Antibiotic susceptibility of lactic acid bacteria (LAB) isolated from malaysian fermented foods - Siti Nasiroh, Ismail; Nina Suhaity, Azmi; Makky, Essam A. (2018)
One of important probiotic properties of Lactic Acid Bacteria (LAB) is the ability to resist towards antibiotics. However, the antibiotic susceptibility of LAB associated in Malaysian fermented foods is less explored. Therefore, this study aims to investigate the antibiotic susceptibility of isolated LAB from Pekasam (fermented fish), jeruk maman (fermented vegetable), tapai (fermented glutinuous rice) and tempoyak (fermented durian). Twenty selected strains growth on MRS agar were confirmed LAB by showing negative result in catalase test, gram positive and rod shaped bacteria in gram staining test. All isolated LAB were determined their antibiotic susceptibility towards Penicillin, Ampicillin, Kanamycin, Vancomycin, Streptomycin, Tetracylin, Chloramphenicol and Rifampicin. All strains showed different degree of resistance towards all eight antibiotic used. Three LAB strains which were P-8, P-1 isolated from pekasam and M-3 isolated from jeruk maman showed ability to resist towards all antibiotics used. It can be concluded that the results obtained from this study could contribute to the potential use of isolated LAB as a probiotic in the food and pharmaceutical industries.